Untangling the Indonesian tangle net fishery: Describing a data‐poor fishery targeting large, threatened rays (Superorder Batoidea). Issue 2 (22nd December 2021) - D'Alberto, Brooke M.; White, William T.; Chin, Andrew; Dharmadi,; Simpfendorfer, Colin A.
Abstract: Shark‐like rays (Order Rhinopristiformes) are among the most threatened families of marine fish, yet little is known about their populations. These rays are normally taken as opportunistic catch in fisheries targeting other species and are thus poorly reported. One exception is the Indonesian tangle net fishery, which targets shark‐like rays. Market surveys of Muara Angke landing site in Jakarta, north‐western Java were conducted between 2001 and 2005, and the landed catch from the tangle net fishery was recorded (the Muara Angke landing site includes landings from more than one fishery). In total, 1, 559 elasmobranchs (sharks and rays) were recorded, comprising 24 species of rays and nine species of sharks. The most abundant species landed were the pink whipray Pateobatis fai and the bottlenose wedgefish Rhynchobatus australiae, the latter being the main target species. Catch composition varied based on differences in species catchability and may also be indicative of localized declines. The fishery was highly selective for larger sized individuals, while smaller size classes of many ray species, including the target species, were also caught in other Indonesian fisheries, resulting in fishing pressure across all age classes. The decline of tangle net vessels in the fishery and the potential shift in catch composition in the Indonesian tangle net fishery increase concerns about the status of shark‐like rays and stingrays in Indonesia.